PENGARUH APLIKASI MONDLY ARABIC TERHADAP PENINGKATAN MUFRADAT DI MA MIFTAHUL ULUM PUNTIR - Fahmiyah, Nuril; Syarifuddin, Syarifuddin (Universitas Muhammadiyah Mataram, 2023)
MA Miftahul Ulum Puntir is one of the Senior High School Islamic in Purwosari Pasuruan which was established since 2011. The basically problem that occurred in this program is the Method that used is not effectively to improve student achievement of language,especially in listening achievement.The research of this research are to know the the effect of mondly arabic application on the increase of mufradat in MA Miftahul ulum puntir.in listening achievement teaching to improve student’s listening achievement to identify sounds of Arabic language that have mean and student ‘s achievement to identify sounds that have most similar pronunciation.The research used quantitative approach and the type was Pre-experiment research with pretest-postest one group. The Instrument that used in this research observations,documentation,and test (pretest-postest). The result of this research is conclude that teaching and learning process thought Mondly Application is influence to improve language achievement especially listening.Based the distributation .This is based on the final result of the paired sample test which has a significance value of less than 0.05, Sig.(0.000)